A dual-channel "on–off–on" fluorescent probe for the detection and discrimination of Fe3+ and Hg2+ in piggery feed and swine wastewater. Issue 23 (31st May 2022) - Fan, Qing; Bao, Guang-Ming; Li, Si-Han; Liu, Si-Yi; Cai, Xin-Ru; Xia, Yi-Fan; Li, Wei; Wang, Xiao-Ying; Deng, Ke; Yuan, Hou-Qun
Abstract : A dual-channel "on–off–on" fluorescent carbon dot was developed for specific detection of Fe 3+ and Hg 2+, which can be distinguished by F − and Al 3+ . The probe was practically applied in quantification of Fe 3+ and Hg 2+ in livestock feed and wastewater. Abstract : Blue-fluorescent blood-CDs were synthesized through a one-pot hydrothermal method using a mixture of chicken blood and trisodium citrate and then explored as a fluorescent probe for detecting Fe 3+ and Hg 2+ . The probe showed excellent selectivity and sensitivity towards Fe 3+ and Hg 2+ with a dramatic "on–off" fluorescence response. F − recovered the fluorescence quenching by Fe 3+, and Al 3+ recovered the fluorescence quenching by Hg 2+, showing an "off–on" fluorescence response. The blood-CDs were used as an "on–off–on" dual-channel fluorescent sensor for the detection and discrimination of Fe 3+ and Hg 2+ ions. The probe showed wide linear ranges for determination of Fe 3+ (0–100 μM) and Hg 2+ (0–120 μM) with low detection limits of 0.23 μM for Fe 3+ and 0.17 μM for Hg 2+ . This probe was practically applied for the determination of Fe 3+ and Hg 2+ in piggery feed and wastewater with good recoveries. This work provides a fluorescent probe for the quantification of Fe 3+ and Hg 2+ in livestock feed and environmental water samples.